Effect of border traps on the threshold voltage instability of fluoride-doped AlGaN/GaN metal–insulator–semiconductor high-electron-mobility transistors. (5th March 2019) - Chang, Li-Cheng; Yin, Shin-Yi; Wu, Chao-Hsin
Abstract: In this paper, we performed a systematic investigation of the threshold-voltage ( V th ) instability of enhancement-mode (E-mode) AlGaN/GaN metal–insulator–semiconductor high-electron-mobility transistors (MIS-HEMTs). The E-mode MIS-HEMTs are firstly demonstrated by using the fluoride plasma treatment and the V th is characterized by 1.55 V after the 400 °C post-metallization annealing (PMA). This PMA which is used to eliminate the interface trap induced by the plasma damage exhibits a trade-off between the negative shift of V th and the performance improvement both for the ON- and OFF-states. Nevertheless, a significant hysteresis occurs even after employing the PMA indicating that either interface traps or border traps in the insulator tend to capture the electrons, wherefore the traps result in a negative net charge. According to this result, both pulsed measurement and stress measurement with DC measurement are implemented to identify the property of the trap state. A significantly positive V th shift is observed both in a long pulsed-width measurement and DC measurement right after the positive gate stress which implies that border traps with a long emission time constant induce a retentive V th even under the DC measurement. Besides, compared to the fluoride-doped HEMT (i.e. HEMT without insulator insertion), fluoride-doped MIS-HEMT exhibiting a more significant V th shift suggest that additional border traps are created through the fluoride ion diffusion during the high temperature annealing.